Watch your workers win: Changing job demands and HRM responses - Luke Haywood (Management Revue, 2011)
This paper considers how the demand for non-material aspects of jobs evolves over changing wealth levels and how firms may want to react. We first consider the importance of non-material job aspects in general before turning to two specific human resource practices: flexible working hour arrangements and employer pension provision. In order to estimate the effect of wealth on job preferences without confounding it with the potential effect of job preferences on wealth due to earnings differentials, we focus on non-labour income (e.g. lottery winnings). We test how it affects workers' preferences using an approach based on duration data.
Keywords: J28; J32; J63; M52; M54; 650; job satisfaction; wealth; HRM; job mobility; turnover